The Management of Acute Uncomplicated Cystitis in Adult Women by Family Physicians in Canada - Warren J McIsaac; Preeti Prakash; Susan Ross (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: There are few Canadian studies that have assessed prescribing patterns and antibiotic preferences of physicians for acute uncomplicated cystitis. A cross-Canada study of adult women with symptoms of acute cystitis seen by primary care physicians was conducted to determine current management practices and first-line antibiotic choices.